Effect of the exposure period and concentration of aqueous and alcoholic zingiber (Zingiber officinale) extract on the mean of mortality for hydatid cyst’s protocolises - Noora Dhyaaldain Abed; Waleed Ahmed Hassen; Hala Yaseen Kadhim; Nagham Yasin Al-Bayati (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the anti-protocolises effect of aqueous and alcoholic zingiber extract. Method: The present experimental study was conducted from 01, July 2021 to 15. December, 2021 at the College of Education for Pure Sciences, Iraq, and comprised 25mg/mL, 50mg/mL, 100mg/mL and 200mg/mL concentrations of both aqueous and alcoholic extracts of zingiber officinale that were prepared and used in vitro on hydatid cyst protocolises with 10min, 20min, 30min, 40min, 50min and 60min exposure times. The data was analysed using statistical package for the social sciences (SPSS) version 10 by using ANOVA and t- test to determine the differences between groups. Results: The concentration of 200mg/ml was more efficient against the protocolises for aqueous extract, while the alcoholic extract was effective at both 100mg/ml and 200mg/ml concentrations. There was a positive relationship of the degree of killing with both exposure time and concentration. Conclusion: Zingiber officinale could be a potential bioactive natural product and its active constituents could be isolated and used as anti-protoscolex without any side effects. Key Words: Zingiber officinale, Echinococcosis, Variance, Ginger